Two Prevalent Listeria ivanovii subsp. ivanovii Clonal Strains With Different Virulence Exist in Wild Rodents and Pikas of China - Gan, Lin; Mao, Pan; Jiang, Huaying; Zhang, Lu; Liu, Dongxin; Cao, Xiaolong; Wang, Yan; Wang, Yiqian; Sun, Hui; Huang, Ying; Ye, Changyun (Frontiers in Veterinary Science, 2020)
Listeria ivanovii subsp. ivanovii is an intracellular bacterium distributed widely in nature, causing the listeriosis in ruminants and humans. Previous researches had isolated 116 strains of L. ivanovii subsp. ivanovii from wild rodents and pikas of different regions in China, and the predominant sequence types were ST1 and ST2. In this study, we first investigated the biological characteristics and virulence of these two clonal strains including motility, metabolism and virulence in cells and mouse model. The results demonstrated the ST1 strains exhibited motility, wide metabolic activity and hypervirulence, whereas the ST2 strains showed non-motility, relative lower metabolic activity and virulence. Considering the transmissible ability from wild rodents and pikas to ecological environment, the L. ivanovii subsp. ivanovii with potential pathogenicity to humans and ruminants should be monitored.